2000
DOI: 10.2169/internalmedicine.39.163
|View full text |Cite
|
Sign up to set email alerts
|

Air Leak Syndrorme as One of the Manifestations of Bronchiolitis Obliterans Organizing Pneumonia.

Abstract: A 46-year-old man developed respiratory distress with air leak syndrome (ALS), including pneumothorax, pneumomediastinum,and subcutaneous emphysema.Openlung biopsy was performed and revealed the histopathologic evidence of bronchiolitis obliterans organizing pneumonia (BOOP), which responded well to steroid treatment. As far as we know, this appears to be the first case ofBOOPpresenting with ALSas one of its major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…In this study, the authors note that spontaneous pneumothorax is a rare complication of OP and may adversely affect prognosis. Another case of OP has been documented that presented as a pneumothorax, pneumomediastinum, and subcutaneous emphysema, and a good outcome was obtained with corticosteroid in this patient (20). In this report, we document the successful management of a patient with COP complicated by air leak syndrome.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this study, the authors note that spontaneous pneumothorax is a rare complication of OP and may adversely affect prognosis. Another case of OP has been documented that presented as a pneumothorax, pneumomediastinum, and subcutaneous emphysema, and a good outcome was obtained with corticosteroid in this patient (20). In this report, we document the successful management of a patient with COP complicated by air leak syndrome.…”
Section: Discussionmentioning
confidence: 69%
“…Pneumothorax and pneumomediastinum presentation in OP patients is rare (20,21). Kofteridis et al (21) reported a fatal case of OP in which a spontaneous pneumothorax de-veloped and the patient failed to survive despite corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other uncommon manifestations include chest pain, night sweats and mild arthralgia (when arthralgia is prominent and/ or associated with myalgia an underlying connective tissue disease should be suspected). Air leak (pneumothorax, pneumomediastinum) may be a rare presenting feature [106,107]. Since the most common manifestations are nonspecific, diagnosis is often delayed (6-13 weeks).…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Eight cases of OP complicated by cyst or pneumothorax formation have been previously reported; however, the causal mechanisms of the development of cyst and pneumothorax formation related to OP have not been clarified (1)(2)(3)(4)(5)(6)(7)(8). Although air-trapping caused by the check-valve mechanism is thought to be a plausible mechanism of cyst and pneumothorax formation, the details of the corresponding pathological changes that occur in air-trapping have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%